Farming Households’ Adaptation Strategies Against Climate Change in the Department of Mono (Southern Benin) - OGOUWALE, EULOGE (My University, 2023)
This article assesses the coping strategies implemented by farming households in the Department of Mono based on a sample of 510 rural households. The article uses descriptive statistics to determine the coping strategies most developed by farming households. Strategies with percentages greater than or equal to 50% are considered to have been adopted by the majority. The results show that 81.96% of farming households in the study area change their agricultural calendar, 73.73% use dry ploughing for semi-early start-up, 80% use collective prayers, 64.71% adopt short-cycle variety crops, 77.65% engage in non-agricultural incomegenerating activities, 55.69% and 58.82% use modified sowing and mulching respectively. The late start and poor distribution of the rains, the increasing frequency of droughts and falling rainfall justify the use of these strategies. In view of these results, there is an urgent need to support rural households in choosing and implementing effective coping strategies against climate change.
Keywords: stratégies; Farming Households; climate; Change; department; Mono And Rural Areas